2020
DOI: 10.33899/ijvs.2020.165812
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silver nanoparticles on some blood parameters in rats

Abstract: The present study aims are investigating the effects of oral administration of AgNPs on some blood the parameters to show potential of toxicity of AgNPs as tool therapy and diagnosis. In this study, 20 healthy male and female rats were used. Randomly, rats were divided into 5 groups depending on the period variable respectively; AgNPs-treated rats' groups for a period of 3 days in concentration 0.2 and 0.4 gm/kg B.W, while the second period after 20 and 30 days after treatment with concentration 0.08 and 0.008… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 20 publications
3
10
0
Order By: Relevance
“…The histopathological changes of the lungs showed sloughing of epithelial lining the bronchi bronchopneumonia, edema, emphysema, and fibrinous edema that result agreement with another study which found that acute pulmonary toxicity and tumor promotion by the food additive 2,6-di-tert-butyl-4-methylphenol (BHT) are well documented to cause lung lesions (27,28). These suggest the possibility that BHT may exert their promoting effects by inducing oxidative stress, normal cells are destroyed more readily which allows neoplastic cells to expand their proliferation (29,30). Our interpretation for that is the high doses or reheated of BHT are produce lung damage due to some BHT metabolites that are conjunction with SH-groups for proteins like cysteine protein and also inhibit glutathione formation that causes lung toxicity.…”
Section: Discussionsupporting
confidence: 89%
“…The histopathological changes of the lungs showed sloughing of epithelial lining the bronchi bronchopneumonia, edema, emphysema, and fibrinous edema that result agreement with another study which found that acute pulmonary toxicity and tumor promotion by the food additive 2,6-di-tert-butyl-4-methylphenol (BHT) are well documented to cause lung lesions (27,28). These suggest the possibility that BHT may exert their promoting effects by inducing oxidative stress, normal cells are destroyed more readily which allows neoplastic cells to expand their proliferation (29,30). Our interpretation for that is the high doses or reheated of BHT are produce lung damage due to some BHT metabolites that are conjunction with SH-groups for proteins like cysteine protein and also inhibit glutathione formation that causes lung toxicity.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, RBC and HGB levels increased and afterwards increase of HCT, MCV, MCH and MCHC levels were observed in three treatments groups (A, B & C) in comparison with the PC groups. The results of the present study correlate with several reports on the hematotoxic of AgNPs (50,51), and this results were consistent with the Rostami, and Mahdavi on hemathomomodulatory effects of Scrophularia striata studies (37,38).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the levels of vitamin E and selenium were clearly decreased in diseased animals compared with the control group. Vitamin E is considered the main and important antioxidant factor in the body, nevertheless, not all its characterizations could be detected in this action and its main activities are confined to act in cell membranes to prohibit the spreading of free radical interactions and reactions, although it has been also indicated to have prooxidant activities (17,18). On the other hand, it was shown that the non-radical oxidation products could be created through the reaction between alpha-tocopheryl radical and the other free radicals, which are together with glucuronic acid and excreted through both bile and urine.…”
Section: Discussionmentioning
confidence: 99%